2020
DOI: 10.1503/cjs.004719
|View full text |Cite
|
Sign up to set email alerts
|

Acute care surgery, trauma and disaster relief: a clinical exchange between the University of British Columbia and the Mexican Red Cross

Abstract: Background: Our objective was to establish a sustainable educational partnership and clinical exchange between the trauma services at Vancouver General Hospital (VGH) and the Mexican Red Cross hospital in Mexico City (Hospital Central de la Cruz Roja [HCCR] Polanco). Methods: In 2017, a general surgery resident in postgraduate year 4 travelled from VGH to HCCR Polanco for the initial exchange, followed by a trauma fellow. The surgical case volumes in a month at VGH and a month at HCCR Polanco were compared. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“… 41 Margolick et al also identified the cost of flights, meal and accommodation as a financial barrier to reciprocity in potential twinning programmes with the HIC partner institution. 39 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 41 Margolick et al also identified the cost of flights, meal and accommodation as a financial barrier to reciprocity in potential twinning programmes with the HIC partner institution. 39 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies (83%) described advantages with visiting surgical teams,17 19–42 further subgrouped into skills improvement, immediate clinical patient care, system-level strengthening, academic and career benefits and broader collaboration opportunities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations